Improved calcium sensor GCaMP-X overcomes the calcium channel perturbations induced by the calmodulin in GCaMP - Yang, Yaxiong; Liu, Nan; He, Yuanyuan; Liu, Yuxia; Ge, Lin; Zou, Linzhi; Song, Sen; Xiong, Wei; Liu, Xiaodong (Nature communications, 2018)
GCaMP, one popular type of genetically-encoded Ca 2+ indicator, has been associated with various side-effects. Here we unveil the intrinsic problem prevailing over different versions and applications, showing that GCaMP containing CaM (calmodulin) interferes with both gating and signaling of L-type calcium channels (Ca V 1). GCaMP acts as an impaired apoCaM and Ca 2+ /CaM, both critical to Ca V 1, which disrupts Ca 2+ dynamics and gene expression. We then design and implement GCaMP-X, by incorporating an extra apoCaM-binding motif, effectively protecting Ca V 1-dependent excitation–transcription coupling from perturbations. GCaMP-X resolves the problems of detrimental nuclear accumulation, acute and chronic Ca 2+ dysregulation, and aberrant transcription signaling and cell morphogenesis, while still demonstrating excellent Ca 2+ -sensing characteristics partly inherited from GCaMP. In summary, CaM/Ca V 1 gating and signaling mechanisms are elucidated for GCaMP side-effects, while allowing the development of GCaMP-X to appropriately monitor cytosolic, submembrane or nuclear Ca 2+ , which is also expected to guide the future design of CaM-based molecular tools. The popular genetically-encoded Ca 2+ indicator, GCaMP, has several side-effects. Here the authors show that GCaMP containing CaM interferes with gating and signaling of L-type calcium channels, which disrupts Ca 2+ dynamics and gene expression, and develop GCaMP-X to overcome these limitations.